Student Participation in University Governance - Zuo, Bing; Ratsoy, Eugene W. (Canadian Journal of Higher Education, 1999)
This study investigated the scope, process, and effects of student participation in university governance, including student government. The study demonstrated that students are capable of administering their own affairs, satisfying various student needs, and protecting the political interests of students. Students were extensively involved in university academic and administrative decision-making at different levels. However, student associations as organized forces had much greater influence than did students at large. Both environmental and personal factors affected the impact of student participation in university governance. Although student participation in university governance is deemed indispensable, student participants must hone their group decision-making skills and demonstrate commitment to the mission of the university and its long-term interests.